The Emergence of the Bohemian State - CJ Nicholson (Slovo, 2012)
Nicholson, CJ (2012) The Emergence of the Bohemian State. [Series: East Central and Eastern Europe in the Middle Ages, 450–1450.] By PETR CHARVÁT. Pp. 235. Leiden: Brill. 2010. $153. Cloth. ISBN 9789004180093. [Review]. Slovo , 24 (2). Click here to read the review.